The Effect of Osseous Valgus Alignment and Posteromedial Ligament Complex Deficiency on ACL Graft Forces: Risk Factors for Failure of ACL Reconstruction. Issue 5 (28th May 2020) - Mehl, Julian; Otto, Alexander; Kia, Cameron; Obopilwe, Elifho; Cote, Mark; Imhoff, Florian; Feucht, Matthias J.; Imhoff, Andreas B.; Arciero, Robert A.; Beitzel, Knut
Aims and Objectives: Dynamic valgus moments are known risk factors for ACL (re-)injuries. However, the association between osseous valgus alignment and ACL stress is not fully understood. The aim of the present study was to biomechanically investigate the influence of osseous valgus alignment, with and without deficiency of the medial collateral ligament and posterior oblique ligament (= posteromedial ligament complex; PMC), on ACL-graft forces under axial load. Additionally, it was investigated whether PMC reconstruction alone, correction osteotomy alone or a combination of both procedures were capable to decrease ACL-graft forces. Materials and Methods: The native ACL was dissected and ACL reconstruction was performed on ten cadaveric knee joints. A lateral distal femur osteotomy was done to adjust for three different alignment conditions according to the position where the axial weight bearing line (WBL) dissected the tibial plateau (% from medial to lateral): straight leg (50%), medium valgus (85%) and high-grade valgus (115%). Each alignment condition was tested with the PMC intact, deficient and reconstructed. The specimens were placed in a testing rig in 15° of knee flexion with the tibia fixed and the femur mobile on an X-Y-table. Axial loads of 400 N were applied and changes of ACL-graft forces (via an attached load-cell) and dynamic valgus angle (DVA) (via 3D motion tracking) were recorded. Results: In the PMC intact state, lateralization of the WBL to 85% and to 115% led to significantly increased ACL graft forces (85% vs. 50%: 96.1 ± 25.0 N vs. 63.7 ± 22.0 N, p=0.010; 115% vs. 50%: 109.9 ± 24.5 N vs. 63.7 ± 22.0 N; p<0.001) and DVA (85% vs. 50%: 2.0 ± 1.2° vs. 0.0 ± 0.8°, p=0.027; 115% vs. 50%: 2.1 ± 1.3° vs. 0.0 ± 0.8°; p=0.027). Dissection of the PMC led to a significant increase of ACL graft forces and DVAs at 85% and 115% valgus alignment (p<0.001), but not at 50% alignment. In valgus aligned knees (85%) with additional PMC deficiency, reconstruction of the PMC alone was able to significantly decrease ACL graft forces (85% deficient vs. 85% reconstructed: 158.0 ± 47.3 N vs. 112.1 ± 28.8 N; p<0.001) and DVA (85% deficient vs. 85% reconstructed: 7.4 ± 4.0° vs. 3.0 ± 2.0°; p<0.001). However, alignment correction alone was significantly more effective in reducing ACL graft forces (85% reconstructed vs. 50% deficient: 112.1 ± 28.8 N vs. 81.5 ± 23.8 N, p<0.001) and DVA (85% reconstructed vs. 50% deficient: 3.0 ± 2.0° vs. 0.81.0°; p=0.010). These relations were similar for high grade valgus alignment (115%). Conclusion: Osseous valgus alignment led to significantly increased ACL graft forces and DVA under axial joint compression, which was even further enhanced, when the PMC was deficient. In the valgus aligned and PMC deficient knee, correction to a straight leg axis was significantly more effective in decreasing forces on the ACL graft than reconstruction of the PMC.